EFFECT OF SODIUM DODECYLBENZENESULFONIC ACID (SDBS) ON THE GROWTH RATE AND MORPHOLOGY OF BORAX CRYSTAL - Suharso Suharso (Universitas Gadjah Mada, 2007)
An investigation of the effect of sodium dodecylbenzenesulfonic acid (SDBS) on both growth rate and morphology of borax crystal has been carried out. This experiment was carried out at temperature of 25 °C and relative supersaturation of 0.21 and 0.74 under in situ cell optical microscopy method. The result shows that SDBS inhibits the growth rate and changes the morphology of borax crystal.